Analysis of Risk Factors Associated with Postpartum Depression Among Postpartum Mothers - Habibah, Minda; Pandia, Veranita; Rusmil, Kusnandi; Susiarno, Hadi; Iskandar, Shelly; Tarawan, Vita Murniati (Jurnal Kesehatan Vokasional, 2025)
Background: Postpartum depression (PPD) is a common mental health disorder affecting mothers, infants, and families.Identifying key determinants is essential for early prevention.Objective: This research aimed to examined factors associated with PPD among mothers within three months postpartum at community health centers in Bandung City.Methods: A cross-sectional study included 184 postpartum mothers selected through multistage random sampling. Validated instruments were employed to collect the data, including the Edinburgh Postnatal Depression Scale, Fatigue Severity Scale, Brief Resilience Scale, and Multidimensional Scale of Perceived Social Support. Univariate, bivariate, and multivariate logistic regression analyses were performed.Results: The prevalence of PPD was 22.8%. In the adjusted model, fatigue (AOR = 4.46; 95% CI: 1.78–11.18), at-risk maternal age (AOR = 3.15; 95% CI: 1.22–8.14), and low resilience (AOR = 1.59; 95% CI: 1.01–2.73) were independently associated with PPD.Conclusion: Improving early detection and incorporating regular mental health evaluations into primary care services may help lessen the impact of postpartum depression.